2020
DOI: 10.1111/tbed.13621
|View full text |Cite
|
Sign up to set email alerts
|

Attributes of HIV infection over decades (1982–2018): A systematic review and meta‐analysis

Abstract: Understanding the risk factors for HIV infection is the foundation of successful preventive strategies, which must bundle sociocultural, behavioural and biomedical interventions to halt disease transmission. We aimed in this study to provide a pooled estimation of HIV risk factors and trace changes across decades in order to drive consensus and accurate assessment of disease transmission risk. We comprehensively searched PubMed, ISI Web of Knowledge, Medline, EMBASE, ScienceDirect, Ovid, EBSCO, Google Scholar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 125 publications
(178 reference statements)
0
20
0
Order By: Relevance
“…The wider treatment coverage and improved adherence among WLH has rapidly reduced AIDS-related deaths among women [ 3 ]. Increased access to highly active anti-retroviral therapy (HAART) shifted HIV from an acute illness to a chronic disease [ 4 ] for women in terms of life expectancy, quality of life, and the opportunity for motherhood [ 5 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…The wider treatment coverage and improved adherence among WLH has rapidly reduced AIDS-related deaths among women [ 3 ]. Increased access to highly active anti-retroviral therapy (HAART) shifted HIV from an acute illness to a chronic disease [ 4 ] for women in terms of life expectancy, quality of life, and the opportunity for motherhood [ 5 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…Second, consider periodic routine microbiological etiology surveillance to guide syndromic management of STIs and minimize misdiagnosis. Third, given that STIs and HIV are synergistic [ 32 , 33 ] and that HIV testing in Tunisia is carried out in a few specific basic care centres and that testing is not systematic for all STI consultants(It is an anonymous test and its acceptance by the community remains limited), we suggest to properly screen for contacts and increase the rigour of HIV testing by systematically referring STI cases to the Centre’s anonymous and free HIV screening.…”
Section: Discussionmentioning
confidence: 99%
“…In addition,selfreporting STIs in the last year and staying in current residence for more than 12 months were signi cantly associated with HIV-1 infection in both LCFSWs and CMFSWs, while staying in current residence for more than 12 months were related to syphilis infection among CMFSWs and LCFSWs, respectively. A metaanalysis reported that STIs as a superior role for contributing to HIV infection [35]. Therefore, there is no doubt that self-reporting STIs has been a associatted factor to HIV infection among FSWs in a decade.…”
Section: Discussionmentioning
confidence: 99%